Oral Capecitabine Compared With Intravenous Fluorouracil Plus Leucovorin in Patients With Metastatic Colorectal Cancer (TAJ: Journal of Teachers Association, 2018)
Patients And Methods: We prospectively randomized 150 patients to treatment with capecitabine 1,250 mg/m2 administered twice daily days 1 to 14 every 3 weeks, or to the 4-weekly Mayo Clinic regimen (5-FU/LV) until disease progression or unacceptable toxicity.Results: The primary objective, to demonstrate at least equivalent response rates in the two treatment groups, was met. The overall response rate was 18.9% for capecitabine and 15.0% for 5-FU/LV. In the capecitabine and 5-FU/LV groups, respectively, median time to disease progression was 5.2 and 4.7 months (log-rank P = .65); median time to treatment failure was 4.2 and 4.0 months (log-rank P = .89); and median overall survival was 13.2 and 12.1 months (log-rank P = .33). The toxicity profiles of both treatments were typical of fluoropyrimidines. However, capecitabine led to significantly lower incidences (P < .00001) of stomatitis and alopecia, but a higher incidence of cutaneous hand-foot syndrome (P < .00001). Capecitabine also resulted in lower incidences (P < .00001) of grade 3/4 stomatitis and neutropenia, leading to a lower incidence of grade 3/4 neutropenic fever and sepsis. Only grade 3 hand-foot syndrome (P < .00001) and uncomplicated grade 3/4 hyperbilirubinemia (P < .0001) were reported more frequently with capecitabine.Conclusion: Oral capecitabine achieved an at least equivalent efficacy compared with IV 5-FU/LV. Capecitabine demonstrated clinically meaningful safety advantages and the convenience of an oral agent.TAJ 2012; 25: 17-25